The relationship between financial leverage and liquidity, and firms' profitability of the agricultural industry: evidence from Malaysian listed firms / Muhamad Adhwa Zulkipli, Nik Anis Idayu Nik Abdullah and Amrizah Kamaluddin. - Zulkipli, Muhamad Adhwa; Nik Abdullah, Nik Anis Idayu; Kamaluddin, Amrizah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
This study examined the relationship between financial leverage and liquidity with firms’ profitability of the Malaysian agricultural industry between 2011 to 2015. Additionally, the study attempted to examine the ability of both financial leverage and liquidity in predicting firms’ profitability. Financial ratios of 40 agriculturural firms’ that were listed in the Bursa Malaysia Main Board were taken as the sample. The selected variables for the study were Debt Equity Ratio (DTE), Interest Coverage Ratio (ICR), Proprietary Ratio (PR), Current Ratio (CuR), Quick Ratio (QR) and Cash Ratio (CsR) as the independent variables whilst Return on Capital Employed (ROCE) was the dependent variable. The study discovered that significant relationships exists between both financial leverage and liquidity and firm profitability. In addition, both financial leverage and liquidity are also significant to explain and predict firms profitability. The results confirm the trade-off theory, which suggests that firm profitability would increase as the level of debt increases, but only to an optimal level where any subsequent increment in the firms’ debt level upon reaching its optimal level would result in the contraction of its profitability.